Stemming the tide: progress towards resolving the causes of decline and implementing management responses for the disappearing mammal fauna of northern Australia - Ziembicki, Mark R.; Woinarski, John C. Z.; Webb, Jonathan K.; Vanderduys, Eric; Tuft, Katherine; Smith, James; Ritchie, Euan G.; Reardon, Terry B.; Radford, Ian J.; Preece, Noel; Perry, Justin; Murphy, Brett P.; et al. (THERYA, 2014)
Recent studies at some sites in northern Australia have reported severe and rapid decline of some native mammal species, notwithstanding an environmental context (small human population size, limited habitat loss, substantial reservation extent) that should provide relative conservation security. All of the more speciose taxonomic groups of mammals in northern Australia have some species for which the conservation status has been assessed as threatened, with 53% of dasyurid, 46% of macropod and potoroid, 33% of bandicoot and bilby, 33% of possum, 31% of rodent, and 24% of bat species being assessed as extinct, threatened or Near Threatened. This paper reviews disparate recent and ongoing studies that provide information on population trends across a broader geographic scope than the previously reported sites, and provides some information on the conservation status and trends for mammal groups (bats, larger macropods) not well sampled in previous monitoring studies. It describes some diverse approaches of studies seeking to document conservation status and trends, and of the factors that may be contributing to observed patterns of decline. The studies reported provide some compelling evidence that predation by feral cats is implicated in the observed decline, with those impacts likely to be exacerbated by prevailing fire regimes (frequent, extensive and intense fire), by reduction in ground vegetation cover due to livestock and, in some areas, by ‘control’ of dingoes. However the impacts of dingoes may be complex, and are not yet well resolved in this area. The relative impacts of these individual factors vary spatially (with most severe impacts in lower rainfall and less topographically rugged areas) and between different mammal species, with some species responding idiosyncratically: the most notable example is the rapid decline of the northern quoll Dasyurus hallucatus due to poisoning by the introduced cane toad Rhinella marina, which continues to spread extensively across northern Australia. The impact of disease, if any, remains unresolved. Recovery of the native mammal fauna may be impossible in some areas. However, there are now examples of rapid recovery following threat management. Priority conservation actions include: enhanced biosecurity for important islands, establishment of a network of substantial predator exclosures, intensive fire management (aimed at increasing the extent of longer-unburnt habitat and in delivering fine scale patch burning), reduction in feral stock in conservation reserves, and acquisition for conservation purposes of some pastoral lands in areas that are significant for mammal conservation.